Archaeological Evidence for the Beginning of the Norse Colony in Greenland - Čuk, Jaka, 1991- (2020)
The Norse who settled Greenland mostly did so in two principal regions, referred to as the Eastern Settlement and the Western Settlement. While written sources provide a narrative about the beginning of the colonization, very few sites have been identified and confirmed as having been settled in the landnám period, broadly defined here as the period 950 to 1050 AD through archaeological excavations. With the application of modern techniques, namely radiocarbon dating, absolute data is now available for some of them. This thesis presents 25 sites, 21 from the Eastern settlement and 4 from the Western settlement, where radiocarbon samples indicate early settlement. The aim is to illustrate how limited the evidence is about the beginning of settlement in Greenland and how little is known for certain about the late Viking Age in this area.